Pharmacotherapy for Social Anxiety Disorder and Posttraumatic Stress Disorder: New Meta-Analytic Approaches to Synthesising the Evidence - Williams,Taryn Amos (Department of Psychiatry and Mental Health, 2022)
Background Social anxiety disorder (SAD) and posttraumatic stress disorder (PTSD) are prevalent, disabling and highly comorbid disorders. SAD is the most prevalent of the anxiety disorders, and PTSD is the central disorder in the DSM-5 section on trauma- and stressor-related disorders. Given the growing need to consider the totality of evidence for pharmacological treatment for SAD, the publication of systematic reviews and of novel meta-analytic approaches have become of interest for the use of medication in their treatment and decision making. This dissertation has three objectives 1) To update Cochrane reviews of pharmacotherapy for SAD and PTSD, 2) To conduct a qualitative systematic review of network meta-analyses for pharmacological treatment of common mental disorders, 3) To conduct network meta-analyses for SAD and for PTSD and to compare findings to standard pairwise meta-analytic methods. Methods To obtain eligible trials to answer each aim, trials were identified through a systematic search of a variety of electronic databases: the Cochrane Common Mental Disorders Controlled Trials Register (CCMDCTR-Studies and CCMDCTR-References), MEDLINE, EMBASE, PsycINFO, Google Scholar, Scopus, PubMed Central, the International Clinical Trials Registry Platform (ICTRP) (apps.who.int/trialsearch), clinicaltrials.gov, the National PTSD Center Pilots database and the metaRegister module [mRCT] of the Controlled Trials database, specific to each aim. RCTs of pharmacological treatments comparing active drug versus active drug or active drug versus placebo for SAD and PTSD were considered for inclusion in the respective chapters, and in answering the aims, with the inclusion of add on trials in the SAD and PTSD NMA reviews. Adult participants (18-65 years) diagnosed with SAD and PTSD according to the Diagnostic Statistical Manual for Mental Disorders (DSM, all versions) were included in the individual reviews (i.e. for chapter two, three, five and six). In chapter three adolescents and adults with common mental disorders (depression, GAD, PD, OCD, PTSD, SAD and specific phobia) diagnosed according to the DSM or the International Classification of Diseases ((ICD- 10) were included. The primary and secondary outcomes across aims and reviews include clinical response rates (i.e. the Clinical Global Impressions Improvement scale (CGI-I) or similar) and acceptability (i.e. dropouts due to side effects); and the investigation of symptom severity for SAD with the Liebowitz Social Anxiety Scale (LSAS) and PTSD with the Clinician Administered PTSD Scale (CAPS). In addition, the proportion of dropouts due to any cause were also assessed. The quality of each trial was assessed according to the Cochrane Risk of Bias Tool. GRADE was also used to grade the quality of evidence for the Cochrane reviews and NMAs and the International Society for Pharmacoeconomics and Outcomes Research checklist of good research practices for indirect treatment-comparison in assessing studies for aim two. For aim one, the extracted data for the SAD and PTSD Cochrane reviews was exported into RevMan 5.3.5. Software, which was used to conduct a meta-analysis for SAD and PTSD separately. Pre-planned subgroup and sensitivity analyses were conducted for each review, as well as the generation of funnel plots to assess publication bias with the Eggers' regression test using the R statistical computing platform for the SAD review. In answering aim three, standard pairwise meta-analyses were performed using a random effects model and Frequentist method in RStudio version 3.5 for the SAD NMA review, and Bayesian method using Markov chain Monte Carlo methods in WinBUGS version 1.4.3 for the PTSD NMA. The P-score, an analogue to the surface under the cumulative ranking curves (SUCRA), was used to rank the treatments on a continuous scale for all pairwise comparisons for the SAD NMA, and for the PTSD review, ranking probabilities using the surface under the cumulative ranking curve (SUCRA) and mean ranks were assessed. Results For aim one, the evidence for the standard pairwise Cochrane reviews of SAD and PTSD were most convincing for the treatment efficacy of SSRIs (number of studies (k) = 24, risk ratio (RR) 1.65; 95% confidence interval (CI) 1.48 to 1.85, N = 4984 and k = 8, RR 1.61; 95% CI 1.41 to 1.84, N = 1078, respectively), and was based on very low quality evidence. Evidence of a benefit for the SSRIs was also observed for the reduction of social anxiety symptoms on the LSAS (k = 14, mean difference (MD) −10.14 points, 95% CI −14.05 to −6.22, N = 1990) and posttraumatic symptoms on the CAPS (k = 14, MD −4.69 points, 95% CI −7.18 to −2.20, N = 2709). Other medications such as SSRIs, the serotonin–norepinephrine reuptake inhibitor (SNRI) venlafaxine, monoamine oxidase inhibitors (MAOIs), reversible monoamine oxidase inhibitors (RIMAs), benzodiazepines, the antipsychotic olanzapine, and the noradrenergic and specific serotonergic antidepressant (NaSSA) atomoxetine were also effective in reducing SAD symptoms, with evidence of a treatment response for anticonvulsants with gamma-amino butyric acid (GABA) analogues, the MAOIs, the RIMAs and the benzodiazepines. For the treatment of PTSD, the alpha-blocker prazosin and antipsychotics reduced symptom severity, and the alpha-blocker prazosin and the tricyclic antidepressant amitriptyline improved number of responders. Overall, SSRIs were less well tolerated than placebo in both reviews (SAD Review: k = 5131, RR 2.59; 95% CI 1.97 to 3.39, N = 5131; PTSD Review: (k = 15, RR 1.41; 95% CI 1.07 to 1.87, N = 2493), but there were low absolute rates of withdrawal compared to placebo (16% and 14%, respectively). There were no significant differences in dropouts due to any cause in both reviews for the SSRI intervention arms (SAD Review: k = 26, RR 1.01; 95% CI 0.90 to 1.14, N = 5208; ; PTSD Review: k = 21, RR 1.13; 95% CI 0.93 to 1.38, N = 3206). Twenty NMAs (i.e. investigating depressive disorder, GAD, SAD, PTSD and OCD) were found in answering aim three, and antidepressants were found to be the most efficacious and tolerable agents for these disorders based on rankings (45% of NMAs) or statistical significance (55% of NMAs). The quality of the reporting of each NMA was high. Seventy percent of the NMAs included a network diagram and 75% of the included NMAs assessed consistency, made use of a random effects model, provided information on the model used to fit the data and adjusted for covariates. The review also revealed that few NMAs reported rankings of treatments. The SAD and PTSD NMA provided similar findings to the Cochrane reviews, discussed in aim one. For aim three (the SAD NMA), the SSRI paroxetine was significantly more effective than placebo in reducing the number of responders (odds ratio (OR) 2.64; CI 1.97 to 3.54) and anxiety symptoms (mean difference (MD) -15.89; CI -29.94 to -1.84) yet performed worse in comparison to placebo for dropouts due to adverse events. Most of the medications (i.e.12 out of 19 comparisons) reported a decrease in dropout rates relative to placebo, but no statistically significant difference was found. There was also evidence that venlafaxine is efficacious in treating SAD symptoms. According to the rankings of individual treatments olanzapine performed better than the rest of the treatments in terms of treatment efficacy and buspirone for dropouts due to any cause. Bromazepam performed well in treating the number of responders due to adverse events. Similarly, for the PTSD NMA, paroxetine was also effective in the treatment of PTSD symptoms (MD -15.89; CI -29.94 to -1.84). Evidence was also observed for phenelzine, desipramine and risperidone for the treatment of PTSD symptoms. Mirtazapine yielded a relatively high rank for efficacy, but the respective value for acceptability was not among the best treatments. Most evidence from both NMAs was associated with low to very low-quality evidence. Conclusion Different meta-analytic approaches are useful in presenting, synthesising, and reporting data. The evidence discussed here suggest that SSRIs are effective in the treatment and reduction of SAD and PTSD symptoms, even though the tolerability of SSRIs was lower than placebo for each disorder. It is noteworthy that similar estimates were found across the different approaches to synthesising data and across the different patient groups (i.e. SAD and PTSD). In addition, the NMAs found in this dissertation show high quality of reporting and that study limitations do not impact on the network estimate. The quality of reporting of individual RCTs included across the review however remain low, and so additional research is needed in this area.